Sustained strain applied at high rates drives dynamic tensioning in epithelial cells - Bahareh Tajvidi Safa; Jordan Rosenbohm; Amir Monemian Esfahani; Grayson Minnick; Amir Ostadi Moghaddam; Nickolay V. Lavrik; Changjin Huang; Guillaume Charras; Alexandre Kabla; Ruiguo Yang (Communications Biology)
Abstract Epithelial cells experience long lasting loads of different magnitudes and rates. How they adapt to these loads strongly impacts tissue health. Yet, much remains unknown about the evolution of cellular stress in response to sustained strain. Here, by subjecting cell pairs to sustained strain, we report a bimodal stress response, where in addition to the typically observed stress relaxation, a subset of cells exhibits a dynamic tensioning process with significant elevation in stress within 100 s, resembling active pulling-back in muscle fibers. Strikingly, the fraction of cells exhibiting tensioning increases with increasing strain rate. The tensioning response is accompanied by actin remodeling, and perturbation to actin abrogates it, supporting cell contractility’s role in the response. Collectively, our data show that epithelial cells adjust their tensional states over short timescales in a strain-rate dependent manner to adapt to sustained strains, demonstrating that the active pulling-back behavior could be a common protective mechanism against environmental stress.